2009
DOI: 10.1073/pnas.0902903106
|View full text |Cite
|
Sign up to set email alerts
|

Wild birds of declining European species are dying from a thiamine deficiency syndrome

Abstract: Wild birds of several species are dying in large numbers from an idiopathic paralytic disease in the Baltic Sea area. Here, we demonstrate strong relationships between this disease, breeding failure, and thiamine (vitamin B1) deficiency in eggs, pulli, and full-grown individuals. Thiamine is essential for vertebrates, and its diphosphorylated form functions as a cofactor for several life sustaining enzymes, whereas the triphosphorylated form is necessary for the functioning of neuronal membranes. Paralyzed ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 33 publications
5
75
0
Order By: Relevance
“…Contrary to the suggestion by Rocke and Barker (1), we do not want to exclude botulism as a part of the investigated wildlife disorder (2), because botulism may be secondary to the thiamine deficiency syndrome. This possibility and the investigations by Neimanis et al (3) (5), and the actual sensitivity in the study by Rocke et al (5) was 35 out of 40 (88%), which is considerably higher than the proportion found among Swedish gulls (3,4).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Contrary to the suggestion by Rocke and Barker (1), we do not want to exclude botulism as a part of the investigated wildlife disorder (2), because botulism may be secondary to the thiamine deficiency syndrome. This possibility and the investigations by Neimanis et al (3) (5), and the actual sensitivity in the study by Rocke et al (5) was 35 out of 40 (88%), which is considerably higher than the proportion found among Swedish gulls (3,4).…”
mentioning
confidence: 68%
“…The omission of four thiamine-treated specimens in the evaluation of the herring gull experiment is carefully and very well motivated (2). Even if this procedure is not accepted, and all specimens are included in the evaluation, there is still a highly significant therapeutic effect of the thiamine treatment [Fisher's exact test, P = 0.0012; our Table S2 (2)].…”
mentioning
confidence: 99%
“…Likewise the eff ect of variable thiaminase activity on thiamine concentrations in juvenile Chinook or coho salmon has not been determined. Therefore knowledge of thiamine and thiaminase activity of potential prey items is important information, not only for Alaskan salmon species, but also for other top predators found to have low thiamine (Balk et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Despite diff erences among species, a common theme has been observed when thiamine defi ciency is present. This often includes reproductive failure, a decline in populations, and multiple hypotheses off ered to explain the reproductive failures observed (see Hill and Nellbring 1999;Brown et al 2005b;Honeyfi eld et al 2008b;Balk et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Andersen and co-workers (Andersen et al, 2012, Wohlfahrt-Veje et al, 2011, 2012aand 2012b demonstrated that exposure of mixtures of pesticides used under regulatory approved situations results in reproductive disorders among greenhouse workers but the main drivers for these effects could not be established. In other cases adverse effects are caused by currently unidentified chemicals (Balk et al, 2009;Fitzsimons et al, 2001). In addition, there are few examples where major contributors of the toxic potential in complex mixtures are identified, and numerous investigations have demonstrated that other substances than those we generally analyze are major contributors (Brack, 2003).…”
Section: Henrik Sundberg Kemimentioning
confidence: 99%